Targeting H3K27me3 demethylase to inhibit Shh signaling and cholesterol metabolism in medulloblastoma growth - Deng, Hongshi; Guo, Xueli; Feng, Na; Luo, Yi; Liu, Bei; Liu, Shuzhen; Wu, Jiang I.; Shi, Xuanming (Frontiers in Oncology, 2022)
Low levels of H3K27me3 are essential for Shh target gene expression and medulloblastoma growth. Since this low level is mainly maintained by Jmjd3, targeting Jmjd3 will be an efficient way to decrease the medulloblastoma growth. Here we show that the small molecule GSK-J4, an inhibitor of Jmjd3, significantly inhibits the Shh target gene expression in Shh model cells NIH3T3 and primary cerebellar neuronal precursors. In vitro primary tumor cultures further indicated that GSK-J4 efficiently reduces Shh-type medulloblastoma growth. With the treatment of GSK-J4, human DaoY tumor cells arrested at G0/G1 phase with decreased cells in S-phase, and the proliferation of tumor cells was significantly inhibited. RNA-seq analysis suggested GSK-J4 additionally constrains the gene expression of cholesterol biosynthesis, as was validated by RT-qPCR analysis. Our results highlighted the possibility that targeting Jmjd3 with GSK-J4 for Shh signalling and cholesterol metabolism is a potential strategy to treat Shh-type medulloblastoma.